Wage Utilization, Household Decision-making and Role Variations: Implications on Gender Relations among Workers of Teza Tea Company, Burundi - TUYIKEZE, Evode; WANDERE, Donald (Advances in Social Sciences Research Journal, 2020)
This paper is abstracted from a larger study that was carried out among workers of Teza Tea Company in the Muramvya Province of Burundi. The main objective of the study was to assess the socio-economic push-factors that drove tea workers to seek employment at Teza, how they utilized their wages, and the way wages accrued impacted on intra-household gender relations. In this regard, the study assumed that income earned by workers was not utilized appropriately thereby impinging negatively on intra-household gender relations – the outcome of the study proving this assumption otherwise. Methods used for data collection included; structured and unstructured interviews in the Survey Method, Focus Group Discussions, Key Informant interviews, Informal Discussions, and Observations. A sample of 150 workers was drawn from the study population by means of disproportional stratified and simple random sampling. Data were analysed quantitatively and qualitatively. The study was guided by among others, the Bargaining Theory of Krishnaraj [1], the Division of Labour Theory of Arora et. al [2], and Agassi’s [3] Marxist orientation. The study found out that prudent use of wages by the workers had positive effects on intra-household gender relations. Specifically, this enhanced inter-spousal bonding and paved way for more or less symmetrical decision-making powers for both men and women within a marriage situation. Finally, the study also found out that as a result of depressed income for the workers, gender roles within families were not rigid and instead, they took an infinite variety form with no specific responsibilities set aside for either gender.